Whole genome sequence of blaNDM and blaKPC co-producing Klebsiella pneumoniae isolate KSH203 with capsular serotype K25 belonging to ST11 from China. (March 2020) - Fu, Li; Wang, Shanmei; Zhang, Zhikun; Hu, Xiaoyan; Zhang, Luhua; Zhu, Baoli; Wang, Guangxi; Long, Hanan; Zhou, Yingshun
Abstract: Objectives: The aim of this study was to characterise a high biofilm-forming capacity, hypermucoviscous, bla KPC and bla NDM co-producing Klebsiella pneumoniae strain (KSH203). Methods: Antimicrobial susceptibility, biofilm formation and hypermucoviscous phenotype were determined by the disk diffusion method, crystal violet staining and positive string test, respectively. Whole-genome sequencing was performed using a PacBio RS II Sequencer. High-quality reads were de novo assembled using Celera Assembler v.8.0. Genome annotation was performed using the NCBI Prokaryotic Genome Annotation Pipeline (PGAP), and the genome characteristics were analysed by bioinformatics methods. Results: Klebsiella pneumoniae strain KSH203 was resistant to all antibiotics tested but was only intermediate-resistant to polymyxin B. This strain showed high biofilm-forming ability and a hypermucoviscous phenotype with serotype K25 belonging to the ST11 clone. KSH203 consists of a 5 464 059-bp single chromosome and four plasmids including pKSH203-NDM (53 144 bp), pKSH203-KPC (159 467 bp), pKSH203-CTX-M-3 (156 910 bp) and pKSH203-qnrS (253 705 bp). A total of 44 antimicrobial resistance genes and a large number virulence-associated genes were identified in the genome of strain KSH203. Conclusion: In this study, we illustrate the whole genome sequence of high biofilm-forming capacity, hypermucoviscous K. pneumoniae isolate KSH203 with capsular serotype K25 belonging to ST11 isolated from a patient in China, which carried a large number of antimicrobial resistance genes and virulence-associated genes. Future studies are needed to be aware of dissemination of this type of strain among environmental, animal and human isolates.